Analysis Of The Effect Of Promotion Mix Implementation On Consumer Decisions In Using Flight Services Pt. Sriwijaya Air Rute Tanjung Karang – Jakarta - Ariyanto Chandra; Meita Pragiwani (Indonesian Journal of Business, Accounting and Management (IJBAM), 2019)
This study is directed to determine the effect of the promotion mix, namely advertising, personal selling, sales promotion, public relations and publication and direct marketing of the decision to use Sriwijaya Air flight services. To answer the objectives set in this study, questionnaires were used as a tool to collect data relating to advertising variables, individual sales, sales promotions, public relations and publications, direct marketing and the decision to use Sriwijaya Air flight services distributed to 155 respondents of Sriwijaya Air passengers. . The collected questionnaire data is then processed using multiple linear regression inferential statistics with SPSS 17. The results of multiple linear regression analysis can be seen that the independent variables include advertising, private sales, sales promotion, public relations and publication, and direct marketing simultaneously have a significant effect on the decision to use Sriwijaya Air flight services. Partially advertising, sales promotion, public relations and publications, direct marketing has a positive and real effect on the decision to use Sriwijaya Air flight services. While personal selling do not have a significant effect on the decision to use Sriwijaya Air flight services. The results of this study can provide input to Sriwijaya Air airlines to improve and make adjustments to the formulation and implementation of the promotional mix strategy to improve the decision to use Sriwijaya Air air transport services which currently can only explain the variation in the dependent variable changes by 29.2%.